Challenges Faced by Women in Learning English Language: A PRISMA Study - Gupta, Puja Kumari; Poudel, Tikaram (Nepalese Linguistics, 2024)
This study reviews the scientific research concentrating on the challenges of women learning English. We followed the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) framework. Based on the secondary data from an axiological perspective, we explore educational barriers, psychological challenges, cultural values, social position, gender identity, and related issues. We discuss the challenges into two axiological categories: social economics and education. The study indicates that limited access to resources and cultural norms discourage women's education, and economic restrictions further complicate acquiring English. We suggest tailored interventions to help women overcome the challenges of effective English learning.